The economics of gambling - Vaughan Williams, Leighton (Routledge, 2003)
Against a background of extraordinary growth in the popularity of betting and gaming across many countries of the world, there has never been a greater need for a study into gambling's most important factor - its economics. This collection of original contributions drawn from such leading experts as David Peel, Stephen Creigh-Tyte, Raymond Sauer and Donald Siegel covers such interesting themes as:*betting on the horses*over-under betting in football games*national lotteries and lottery fatigue*demand for gambling*economic impact of casino gamblingThis timely and comp.